Pembelajaran Sejarah Kebudayaan Islam dalam Kurikulum Pendidikan Islam di Malaysia - Zahrotun Syifaurrohmah; Alkham Nur Ghazali; Rianita Malikhotul Faoziah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Learning the History of Islamic Culture plays an important role within Malaysia’s education system. Its purpose is to help students develop a strong identity and love for their nation. In this subject, students are not merely taught facts or knowledge about past events; they are also taught moral values, ethics, and a wholesome Islamic worldview. Integrating this subject into the education curriculum aims to provide children with a comprehensive understanding of the development of Islam, both across the Nusantara region and throughout Southeast Asia as a whole. This way, students gain a broad perspective. Furthermore, this subject is designed to foster a love for knowledge in children and to encourage them to uphold Islamic teachings throughout their lives. Its teaching methods are adapted to the changing times, ensuring that the material taught remains relevant to current needs. Through learning the History of Islamic Culture, it is hoped that children will understand the role and contributions of Muslim communities in Southeast Asia, and grow up to be individuals of good character, useful to society, and able to live in harmony with others in accordance with Islamic teachings.